Detection of subtle cartilage and bone tissue degeneration in the equine joint using polarisation-sensitive optical coherence tomography. Issue 9 (September 2022) - Goodwin, M.; Klufts, M.; Workman, J.; Thambyah, A.; Vanholsbeeck, F.
Summary: Objective: To explore the ability of polarisation-sensitive optical coherence tomography (PS-OCT) to rapidly identify subtle signs of tissue degeneration in the equine joint. Method: Polarisation-sensitive optical coherence tomography (PS-OCT) images were systematically acquired in four locations along the medial and lateral condyles of the third metacarpal bone in five dissected equine specimens. Intensity and retardation PS-OCT images, and anomalies observed therein, were then compared and validated with high resolution images of the tissue sections obtained using Differential Interference contrast (DIC) optical light microscopy. Results: The PS-OCT system was capable of imaging the entire equine osteochondral unit, and allowed delineation of the three structurally differentiated zones of the joint, that is, the articular cartilage matrix, zone of calcified cartilage and underlying subchondral bone. Importantly, PS-OCT imaging was able to detect underlying matrix and bone changes not visible without dissection and/or microscopy. Conclusion: PS-OCT has substantial potential to detect, non-invasively, sub-surface microstructural changes that are known to be associated with the early stages of joint tissue degeneration.